PENGARUH TOTAL REVENUE DAN LABA BERSIH TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Nawangwulan, Arieska D.; Ilat, Ventje; Warongan, Jessy D.L (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This research aims to find out how the influence of total revenue and net profit against the stock price (study on the manufacturing companies listed on the Indonesia stock exchange). Methods of analysis used was multiple linear regression. The population in this study is taken is the manufacturing companies listed on the Indonesia stock exchange in 2014-2016. The sample was selected using a purposive sampling method with results of 25 companies. The sample was selected using a purposive sampling method with the results of 25 companies. Research results showed total revenue has significantly against the stock price, and net profit also has a significant influence on the price of the stock. The stock price is high then it will attract investors to invest that later can be used to develop the company in the future.Keywords :Â  Total Revenue, Net Profit, Stock Price